Selection and nuclear immobilization of exportable RNAs - Grimm, Christian (The National Academy of Sciences of the USA, 1997)
The intracellular distribution of RNAs depends on interactions of cis-acting nuclear export elements or nuclear retention elements with trans-acting nuclear transport or retention factors. To learn about the relationship between export and retention, we isolated RNAs that are exported from nuclei of Xenopus laevis oocytes even when most RNA export is blocked by an inhibitor of Ran-dependent nucleocytoplasmic transport, the Matrix protein of vesicular stomatitis virus. Export of the selected RNAs is saturable and specific. When present in chimeric RNAs, the selected sequences acted like nuclear export elements in promoting efficient export of RNAs that otherwise are not exported; the pathway used for export of these chimeric RNAs is that used for the selected RNAs alone. However, these chimeric RNAs, unlike the selected RNAs, were not exported in the presence of Matrix protein; thus, the nonselected sequences can cause retention of the selected RNA sequences under conditions of impaired nucleocytoplasmic transport. We propose that most RNAs are transiently immobilized in the nucleus and that release of these RNAs is an essential and early step in export. Release correlates with functional Ran-dependent transport, and the lack of export of chimeric RNAs may result from interference with the Ran system.